2021
DOI: 10.1111/jfpp.16078
|View full text |Cite
|
Sign up to set email alerts
|

Lotus root ( Nelumbo nucifera Gaertn ) flour a novel ingredient for the formulation of traditional unleavened flatbread: Rheological, physical and nutritional characteristics, and sensory attributes

Abstract: Lotus roots (Nelumbo nucifera Gaertn) is a naturally rich source of bioactive compounds that have been known for the prevention of numerous diseases. In the present study, lotus root flour (LRF) was substituted as a wheat flour (WF) at different concentrations (5%,10%, 15%, 20%, and 25% w/w) and its effect on the functional properties, rheological characteristics, antioxidant activity, total phenolic content (TPC), physical properties, nutritional profile, and sensory attributes on flour and un-How to cite thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Phenolic Content DPPH ABTS flour) was reported as 14.43 mg GAE/100 g DW; after 25% lotus root flour blending, the TPC of flatbread increased to 96.48 mg GAE/100 g DW [50]. Due to their complex structure, the antioxidant capacities of grain samples are generally assessed using more than one method.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic Content DPPH ABTS flour) was reported as 14.43 mg GAE/100 g DW; after 25% lotus root flour blending, the TPC of flatbread increased to 96.48 mg GAE/100 g DW [50]. Due to their complex structure, the antioxidant capacities of grain samples are generally assessed using more than one method.…”
Section: Samplementioning
confidence: 99%
“…Compared to the present study, these ABTS values are relatively lower. Saeed et al [50] reported that flatbread prepared from lotus root flour-wheat flour blends showed higher radical scavenging activity (DPPH value) compared to the control (wheat flour flatbread). The DPPH and ABTS values of barley flour-enriched bazlama samples demonstrated the utilization possibility of this cereal to increase the antioxidant capacities of bazlama.…”
Section: Samplementioning
confidence: 99%
“…also known as lotus, Shuiyun, Shuihua, Yingqu, and so on, belongs to the Nymphaeaceae plant, which is a kind of aquatic vegetable widely cultivated in Southeast Asia and the cultivation area and annual yield of China are 4 × 10 5 hm 2 and 1.2 × 10 7 t (Wu et al., 2019), respectively. In recent years, the consumption of lotus rhizomes has gradually increased due to their crisp texture, attractive color, and nutritional value (Saeed et al., 2021). As a highly nutritious aquatic vegetable, lotus rhizome is rich in antioxidant and health‐promoting bioactive substances, such as polyphenols, alkaloids, tannins, and terpenes (Wang et al., 2018; Yi et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the food industry has focused on bakery products, both sweet [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and savoury or similar bread products [15][16][17][18][19][20][21][22][23]. The bakery product market has changed together with modern society and the consequent objective of food industry to meet the consumer's requests in relation to their hedonic and health expectations [24].…”
Section: Introductionmentioning
confidence: 99%